THE RELATIONSHIP BETWEEN LONELINESS, IDENTITY FORMATION, AND SOCIAL MEDIA ADDICTION AMONG UNDERGRADUATE STUDENTS - Obodo, Chiamaka Esther; Onwuekwem, Tobechukwu Rapuluchi (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
The study investigated the relationship between loneliness, identity formation and social media addiction among undergraduate students, one hundred and Forty-Six (146) undergraduate students comprising of 44 males and 102 females with a mean age of 20.78 and S. D of 2.197 were drawn using multi-stage (cluster, simple random: by balloting and purposive) sampling techniques as participants from Enugu state university of science and technology, Enugu. The ulcla loneliness scale, ego identity process questionnaire and bergen social media addiction scale were used for data collection. The researcher adopted a correlational design, a Pearson Moment Coefficient correlation with the aid of the statistical package for the social sciences (SPSS) version 27. Findings revealed that loneliness r= .133 and identity formation r= .101 at p< .05 did not relate to social media addiction. Therapists should work with students to help them understand that as they grow older, there are specific tasks and responsibilities they need to address.